Prevalence of Helicobacter Pylori Infection in El-Beida City - Hanan Eldaffri; Deyaa Mosbah; Mortada Alajamy; Qusai Ali Hussain (Khalij-Libya Journal of Dental and Medical Research, 2023)
Background and objectives: Helicobacter pylori is a spiral-shaped, Gram-negative, microaerophilic rod with four to seven flagella. Infection with H pylori is increasingly recognized as a global issue. It is one of the common causes of gastritis and peptic ulcers and has been considered a risk factor for gastric cancer. Oral-oral or fecal-oral route is the most common route of H pylori infection. Mainly, there are two types of investigations for detecting the presence of H pylori non-invasive and invasive methods. Aims. This study determines the prevalence of H Pylori among people in El -Beida city and correlates the rate of infection between both sexes in different age groups. Methods. To achieve the aim of this study, random samples (1600) were collected from five local laboratories and the method of investigation was a stool antigen test. The data collected and analyses were performed using Microsoft excel. Results. Out of 1600 cases, 386 tested positive for H pylori with an overall incidence of 24.12%. Rate of infection in males was 24.6% while in females 23.9%. Additionally, the following percentage rates were found in various age group. 0-10 years (20.5 %); 11-20 years (20.9 %); 21-30 years (25.4 %); 31-40 years (25.8 %); 41-50 years (26.04 %); 51-60 years (27.9 %); 61-70 years (15.6 %); 71-80 years and (18.2 %); >80 years (20 %). Conclusions. The prevalence of H. pylori in El Beida city seems to be the same in both genders. The incidence of H pylori infection varies in different age groups, where the highest rate of infection was in the age range (21-40) years and the lowest rate of infection after 70 years old.